Processed glider data: 9 months of hydrographic and ADCP observations in the Gulf of Oman. - Font, Estel; Queste, Bastien (University of Gothenburg, 2024)
68 repeat transects and 2 virtual moorings covering a spring/neap cycle collected by a SeaExplorer glider with T, S, O2, Chl, Optical backscatter, PAR and ADCP data in the Gulf of Oman. Dataset collected as part of the ONR Global project "Shelf slope dyanmics in the Sea of Oman: How submesoscale processes control food and water security". The glider was deployed from the north shore of Oman into the Gulf of Oman, sampling down to 1000m in the oxygen minimum zone.

File and variable metadata included in the netCDF files.

sea057_M##.ad2cp.#####.nc : Raw ADCP data provided in Nortek .nc format. (version 1.0)

SEA057_glider.nc : SeaExplorer data timeseries QC'd and processed into a 1Hz timeseries. (version 1.0)

SEA057_ADCP_v2.nc : ADCP data fully processed, binned (2 dbar) and referenced, and then reprojected back onto a timeseries. ADCP data processed as per https://github.com/bastienqueste/gliderad2cp . (version v3)
Keywords: Glider; ADCP; Gulf of Oman; Oceanography; Persian Gulf Water; Transport; Oxygen Minimum Zones; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser